In Vivo Analysis of MEF2 Transcription Factors in Synapse Regulation and Neuronal Survival - Akhtar, M. Waseem; Kim, Mi-Sung; Adachi, Megumi; Morris, Michael J.; Qi, Xiaoxia; Richardson, James A.; Bassel-Duby, Rhonda; Olson, Eric N.; Kavalali, Ege T.; Monteggia, Lisa M. (PLOS ONE, 2012)
MEF2 (A–D) transcription factors govern development, differentiation and maintenance of various cell types including neurons. The role of MEF2 isoforms in the brain has been studied using in vitro manipulations with only MEF2C examined in vivo. In order to understand specific as well as redundant roles of the MEF2 isoforms, we generated brain-specific deletion of MEF2A and found that Mef2aKO mice show normal behavior in a range of paradigms including learning and memory. We next generated Mef2a and Mef2d brain-specific double KO (Mef2a/dDKO) mice and observed deficits in motor coordination and enhanced hippocampal short-term synaptic plasticity, however there were no alterations in learning and memory, Schaffer collateral pathway long-term potentiation, or the number of dendritic spines. Since previous work has established a critical role for MEF2C in hippocampal plasticity, we generated a Mef2a, Mef2c and Mef2d brain-specific triple KO (Mef2a/c/dTKO). Mef2a/c/d TKO mice have early postnatal lethality with increased neuronal apoptosis, indicative of a redundant role for the MEF2 factors in neuronal survival. We examined synaptic plasticity in the intact neurons in the Mef2a/c/d TKO mice and found significant impairments in short-term synaptic plasticity suggesting that MEF2C is the major isoform involved in hippocampal synaptic function. Collectively, these data highlight the key in vivo role of MEF2C isoform in the brain and suggest that MEF2A and MEF2D have only subtle roles in regulating hippocampal synaptic function.